ANALISIS PERBANDINGAN KEBIJAKAN PENDIDIKAN DASAR ANTARA INDONESIA DAN THAILAND TAHUN 2009-2013 - Mouliza Kristhopher Donna S; Priyatno Harsasto; Sulistyowati . (Journal of Politic and Government Studies, 2015)
International assessments on education show that the basic education qualityof Indonesia is still left behind other countries, one of them are Thailand. The success of Thailand education reform is interesting enough to be examined because those twocountries have some mutual backgrounds, but nowadays Thailand comes up and has better quality in basic education than Indonesia. By this research, the writer wants to explain how the basic education inIndonesia and Thailand work, so that it can give different outputs. The writer limits the problem to the scope of structure in basic education, the role of some agencies inbasic education policy and also the role of historical contexts in each country in supporting the success of the policy. Those three questions will be explained in theframe of education decentralization in Indonesia and Thailand. By using interview and documentary study as the data collection method andbased on Giddens though called Structuration Theory, the writer found that some distinctions such as different definition about education decentralization, actors inthe policy formulation process, education resources, and the relevance behavior between policy formulator and policy implementator, will give impact to the basiceducation structure flexibility. Based on the theory and the finding, it can be inferredthat the structure in education policy in Thailand is better than in Indonesia. It can enable the success of basic education in Thailand. It can be shown from the adequate resources to support the implementation of basic education in Thailand which isbetter than Indonesia’s. The historical contexts in Thailand also can be somethingthat will always remain the policy actor, the formulator and the implementator one, to commit to do the best to bring Thailand’s better life by education. While in Indonesia some of the policy implementator behaviors are still irrelevant with the behavior of the formulator which is democratic, flexible, and responsive